If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(-5) + -3y = -6 Multiply -3 * -5 15 + -3y = -6 Solving 15 + -3y = -6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -3y = -6 + -15 Combine like terms: 15 + -15 = 0 0 + -3y = -6 + -15 -3y = -6 + -15 Combine like terms: -6 + -15 = -21 -3y = -21 Divide each side by '-3'. y = 7 Simplifying y = 7
| 6y-0.8=7y | | 2+5x=5-4x | | 9(x-6)=8x-1 | | 8x-7=9x-6 | | -9(z-1)=-8z-4 | | 15+16x= | | 28+3y=28 | | .91(8000-y)+.97y=7800 | | 15x+16=x | | n*2-23=0 | | -l-19l-1-23-2= | | -19l-l-23-2= | | 5y^2-16+11=0 | | -4(-6)+y=29 | | -91=9t+8 | | 7x^3-x^2-112x+16=0 | | x+(x*.15)=27.6 | | 5(8c-1)-12=38c+5 | | .50(10x-2)=4 | | 34-52(12n-34)+235=32+101(35n-1) | | x^3+2x=110 | | 26a+26b= | | 15s^2+32s-7=0 | | 146-3x=33x+18 | | 11-9x=175-37x | | 0.0625x^2-0.125x=1 | | x^2-2x+1=8 | | 18x-(2x-8)=40 | | 37-3x=6x+27 | | 68-4x=8x-20 | | 7-8x=127-29x | | -10=-5(t-8) |